LncRNA PVT1 promotes proliferation and invasion through enhancing Smad3 expression by sponging miR-140-5p in cervical cancer - Chang, Qing-Qing; Chen, Chun-Yan; Chen, Zhao; Chang, Shuai (Radiology and oncology, 2019)
Background Cervical cancer is one of the most frequent malignancies among females worldwide. Increasing evidence have indicated the participation of long noncoding RNAs (lncRNAs) in the progression and metastasis of cervical cancer. Our present study was conducted to explore the effects of lncRNA plasmacytoma variant translocation 1 (PVT1) on the progression of cervical cancer and the underlying mechanisms. Materials and methods Expressions of PVT1, miR-140-5p and Smad3 in cervical cancer cell lines were detected by qRT-PCR and western blotting. Bioinformatics analysis and luciferase assays were used to elucidate the potential correlations between PVT1, miR-140-5p and Smad3. The roles of PVT1 on the progression of cervical cancer cells were determined by transfecting sh-RNA through series function assays such as colony formation assay, wound healing assay, transwell assay. Results PVT1 and Smad3 were upregulated, and miR-140-5p was downregulated in cervical cancer cells. PVT1 could bind directly with miR-140-5p, and Smad3 was a downstream target of miR-140-5p. Inhibition of PVT1 could enhance expression of miR-140-5p, inhibit the expression of Smad3, significantly inhibited the proliferation, migration, invasion in cervical cancer cells. While transfection of miR-140-5p inhibitor could partially reverse the above changes in cervical cancer cells. Conclusions The results revealed that PVT1 could promote the proliferation and metastasis via increasing the Smad3 expression by sponging miR-140-5p, which might be a promising prognostic and therapeutic target for cervical cancer.